1993
DOI: 10.1038/bjc.1993.174
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 cDNA transfected Lewis lung carcinoma cells show unaltered net tumour growth rate but cause weight loss and shortened survival in syngeneic mice

Abstract: Summary HuIL-6 cDNA, cloned into a neomycin resistant conferring expression vector, BMGNeo, was transfected into Lewis Lung Carcinoma (LLC) cells. LLC cells (5 x 106 ml-X) transfected with IL-6 cDNA (LLC-IL6) secreted IL-6 into the culture supernatant at a concentration of 9.9 ngml-' within 48 h. When 1,000,000 of untransfected LLC, BMGNeo vector transfected LLC (LLC-Neo) or LLC-1L6 cells were transplanted into C57BL/6 mice subcutaneously, the mean ± s.d. of survival times of these mice were 33.3 ± 9.7, 34.3 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…The circulating concentrations of interleukin 6 were consistently higher in the group with at least 5% weight loss compared with the group without weight loss. Recent animal work (Strassman et al, 1992;Ohe et al, 1993) indicates that interleukin 6 has a pivotal role in the development of cancer cachexia. The circulating concentrations of interleukin 6 were consistently higher in the group with at least 5% weight loss compared with the group without weight loss.…”
Section: Methodsmentioning
confidence: 99%
“…The circulating concentrations of interleukin 6 were consistently higher in the group with at least 5% weight loss compared with the group without weight loss. Recent animal work (Strassman et al, 1992;Ohe et al, 1993) indicates that interleukin 6 has a pivotal role in the development of cancer cachexia. The circulating concentrations of interleukin 6 were consistently higher in the group with at least 5% weight loss compared with the group without weight loss.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, though in vitro proliferation of IL-6-expressing WAC2 clones was not substantially di erent from that of the parental and control WAC2 clones, their xenograft tumor growth rate was decreased and correlated with a statistically signi®cant reduction in the number of new capillaries. Previous overexpression of IL-6 cDNA in Lewis lung carcinoma cells did not alter the growth rate of syngeneic tumors (Ohe et al, 1993) suggesting that, indeed, IL-6 might play an important role in the balance of angiomodulators in the vicinity of N-myc ampli®ed neuroblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…One of these factors, IL-6, is a pleiotropic cytokine physiologically involved in the differentiation of myeloid and neuronal cells, and pathologically involved in the early host response to infection and injury (Kishimoto, 1989), in the proliferation of myeloma (Kawano et al, 1988), urological cancer cells (Miki et al, 1989;Okamoto et al, 1997a,b) and possibly breast cancer cells (Chiu et al, 1996), and in the development of hypercalcaemia and osteolytic metastases (De La Mata et al, 1995). A series of studies have suggested that IL-6 secreted from tumour cells is one of the cachectic factors in animal models of murine colon cancer or of xenograft tumours in athymic nude mice (Greenberg et al, 1992;Strassmann et al, 1992b;Ohe et al, 1993;Fujimoto-Ouchi et al, 1995;Yasumoto et al, 1995;Billingsley et al, 1996;Kajimura et al, 1996;Mori et al, 1996;Ohira et al, 1996;Tsujinaka et al, 1996). Recently, clinical reports have also suggested that elevated IL-6 levels in the sera of patients with oesophageal cancer correlate with their bodyweight loss (Oka et al, 1996), and that a decrease in serum IL-6 levels induced by medroxyprogesterone acetate (MPA) correlates with a reversion of bodyweight loss in patients with advanced breast cancer (Yamashita et al, 1996).…”
mentioning
confidence: 99%